PENERAPAN ASAS DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK TERHADAP ANAK-ANAK YANG MELAKUKAN TINDAK PIDANA PENCURIAN - antoni antoni (Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT Handling children in conflict with the law is often equated with handling criminal acts committed by adults in general. In order to tackle juvenile delinquency (delinquency), legally in Indonesia it has been regulated in various kinds of laws and regulations. One of them is Law Number 3 of 1997 concerning the Juvenile Justice System, the presence of this law is considered to be more likely to use formal jurisprudence by emphasizing retributive punishment. The paradigm of arrest, detention and imprisonment of children has the potential to limit freedom and deprive children of their independence. However, over time criminal cases committed by children in conflict with the law can be resolved using a new mechanism, namely the Diversion system adopted from The Beijing Rules which uses a restorative justice approach. So in this article the author will examine further how to apply the concept of diversion in the juvenile criminal justice system in Indonesia, especially in dealing with the crime of theft where the perpetrators are children. This type of research is of a normative juridical nature to examine laws and regulations in the Juvenile Criminal Justice System, especially the application of the principle of diversion. The type of data used is qualitative data and the data sources used are secondary data using an approach to legal material sources, namely: primary, secondary and tertiary. The results of the research concluded that the application of the diversion principle in the juvenile criminal justice system, especially the resolution of criminal acts of theft committed by children, is carried out with an agreement between the parties involved and expressed in the form of a decision. Prior to this determination, diversion had first been attempted. With this diversion, efforts are made for mediation that will lead to a peace (accord) or settlement between the perpetrator and the victim in accordance with the losses incurred, this is considering that the future of the child is prioritized as the next generation and considering that psychologically children are still not worthy of dealing with the law. Keywords: Diversion, Juvenile Criminal Justice System, Theft.